DEVELOPMENT OF STEM EDUCATION: EXPERIENCE OF WORLD LEADERS - Sergiіenko, Tetiana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article examines the impact of the development of STEM education on the modern educational space, taking into account its key role in technological progress. The experience of world leaders in this field, who actively use innovative teaching methods and create favorable conditions for the development of STEM competencies among students and students of higher education, paying attention not only to specific subjects, but also to the development of critical thinking and creative approaches, is considered. Countries that are leaders in STEM education are actively cooperating to share best practices and create international partnerships that help improve the quality of education. It was concluded that the implementation of the successful experience of world leaders in STEM education is a strategic step in preparing young people for the requirements of the modern technological environment.